Inadvertent mental excitement after ultrasound‐guided bilateral thoracic paravertebral block: a case report. Issue 1 (28th March 2021) - Ye, Mao; Zhou, Hong‐Su; Wei, Yi; Liu, Fei
Abstract : Background: Bilateral Paravertebral block has been used successfully for postoperative pain relief in thoracic, abdominal, and pelvic regions. Despite the need for relatively large doses of local anaesthetics, there are few reports of systemic toxicity. Here we reported a case of local anaesthetic toxicity after ultrasound‐guided bilateral thoracic paravertebral block before general anaesthesia leading to mental. To our knowledge, the onset of this patient has never been reported previously, and we will discuss the potential risk factors and preventive measures for such patients in the future. Case information: A 38‐year‐old female patient presented for elective open resection of liver tumor, when bilateral 7th thoracic (T7) paravertebral blocks were performed under the guidance of ultrasound with 0.5% ropivacaine (3 mg/kg) in the anesthesia preparation area. After 20 minutes, the patient suddenly became extremely excited and requested to suspend the operation, because Guanyin Bodhisattva just told her that the operation would put her life in danger. Conclusion: Although the dose of ropivacaine was up to 3 mg/kg for lumbar epidural, or 4.3 mg/kg for major nerve block based on the manufacturer's recommendation, we believe that the bolus dosage of 0.5% ropivacaine 3 mg/kg was high for bilateral thoracic paravertebral block in this patient.